Helicobacter pylori and the Role of Lipopolysaccharide Variation in Innate Immune Evasion - Sijmons, Daniel; Guy, Andrew J.; Walduck, Anna K.; Ramsland, Paul A. (Frontiers in Immunology, 2022)
Helicobacter pylori is an important human pathogen that infects half the human population and can lead to significant clinical outcomes such as acute and chronic gastritis, duodenal ulcer, and gastric adenocarcinoma. To establish infection, H. pylori employs several mechanisms to overcome the innate and adaptive immune systems. H. pylori can modulate interleukin (IL) secretion and innate immune cell function by the action of several virulence factors such as VacA, CagA and the type IV secretion system. Additionally, H. pylori can modulate local dendritic cells (DC) negatively impacting the function of these cells, reducing the secretion of immune signalling molecules, and influencing the differentiation of CD4+ T helper cells causing a bias to Th1 type cells. Furthermore, the lipopolysaccharide (LPS) of H. pylori displays a high degree of phase variation and contains human blood group carbohydrate determinants such as the Lewis system antigens, which are proposed to be involved in molecular mimicry of the host. Lastly, the H. pylori group of outer membrane proteins such as BabA play an important role in attachment and interaction with host Lewis and other carbohydrate antigens. This review examines the various mechanisms that H. pylori utilises to evade the innate immune system as well as discussing how the structure of the H. pylori LPS plays a role in immune evasion.